1967
DOI: 10.3133/pp530
|View full text |Cite
|
Sign up to set email alerts
|

The geologic occurrence of monazite

Abstract: Stream and beach deposits __________ -268 Washington____________________________ 269 West Virginia__________________________ 270 Wyoming______________________________ Fossil placers of Cambrian age________ 271 Fossil placers of Late Cretaceous age__

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
9

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(89 citation statements)
references
References 21 publications
1
79
0
9
Order By: Relevance
“…Several workers have stressed the effect of excess initial 23°Th on 2°~pb-23SU ages [13,15,23]. For SW-121 monazites analysed by TIMS (Table 1), the 2°6pb-23SU age is < 4 Ma greater than the 2°Tpb-235U age [19].…”
Section: Cp Dewolf Et Al / Earth and Planetary Science Letters 120mentioning
confidence: 99%
See 2 more Smart Citations
“…Several workers have stressed the effect of excess initial 23°Th on 2°~pb-23SU ages [13,15,23]. For SW-121 monazites analysed by TIMS (Table 1), the 2°6pb-23SU age is < 4 Ma greater than the 2°Tpb-235U age [19].…”
Section: Cp Dewolf Et Al / Earth and Planetary Science Letters 120mentioning
confidence: 99%
“…Second, the monazite inclusions show no textural or chemical evidence for resorption or overgrowths as would be expected if they were detrital and had been exposed to low grade metamorphic conditions where monazite may be unstable. Instead, they are typical in size (< 50 /zm), morphology (round to tabular with aspect ratio less than 2), and chemistry to monazites from other upper amphibolite grade terranes [13,15,21,27]. Third, the age range of the monazite inclusions overlaps the concordia U-Pb age of two zircons analysed by TIMS [19] which have a rounded, football-shaped, morphology indicative of metamorphic origin.…”
Section: Relation Of Inclusions To Garnet Growth and Closurementioning
confidence: 99%
See 1 more Smart Citation
“…The elevated Th contents in the Kovela complex was most probably resulted from a complex, multi-stage process which involved primary magmatic crystallization and superimposed metamorphic-hydrothermal alteration. Förster and Harlov [69], Overstreet [70], Mohr [71] and Kelly et al [72] suggested that metamorphism may generate the breakdown of primary monazite to Th-rich mineral in the monazite-huttonite series by depletion of the Y, HREE, Ca and P content parallel with the relatively enrichment of Th, Si and LREE. …”
Section: Kovela Granitoid Complexmentioning
confidence: 99%
“…Pb diffusion in the structure of monazite is very low under crustal environments (e.g., Cherniak et al, 2004, Gardés et al, 2007, and it presents relatively wide distribution in continental crust. Monazite appears as primary accessory phase in several igneous, average-to high-grade metamorphic, pegmatite, and diverse hydrothermal rocks; as a detritic phase, in psamitic sediments and rocks (e.g., Overstreet, 1967;Chang, Howie, Zussman, 1998). An unusual occurrence is described in lunar basalts by Lovering et al (1974).…”
Section: Introductionmentioning
confidence: 99%